Injuries in youth volleyball players at a national championship: Incidence, risk factors, and mechanisms of injury - Vaandering, K.; Meeuwisse, D.; MacDonald, K.; Eliason, P. H.; Graham, R. F.; Chadder, M. K.; Lebrun, C. M.; Emery, C. A.; Schneider, K. J. (Clinical Journal of Sport Medicine, 2023)
Objective: To evaluate injury incidence rates, types, mechanisms, and potential risk factors in youth volleyball.